Diseño de productos turísticos como contribución a la valoración cultural de los recursos patrimoniales gastronómicos de la zona sur de Manabí - Bravo Ortiz, Carlos Alexander (2024)
The main objective of this research was to design a tourism product that values the gastronomic heritage of the cantons in the southern zone of Manabí. The research was exploratory and non-experimental, based on a literature review and field research. It was developed in three phases: situational diagnosis, tourism market study, and establishment of the tourism product. In the first phase, the local gastronomy was characterized, identifying it as a fundamental economic and cultural pillar, promoted through gastronomic fairs. However, it faces challenges such as the loss of traditional methods, lack of innovation, social insecurity, and competition from other destinations. The second phase consisted of a study of tourism supply and demand, highlighting the diversity and value of local gastronomy with emblematic dishes such as "tonga" and chicken stew, although tourists prefer seafood products. In the third phase, the mission, vision, objectives, and strategies of the gastronomic product were defined. These strategies were validated and focused on digital marketing and balanced prices to promote the local culinary offer. In conclusion, although the province of Manabí has a rich gastronomic variety recognized in fairs, it is necessary to implement complementary strategies to increase its recognition and appreciation.